The Complex Meaning of Identity Represented in "Wei" by Samuel Rustandi - Sihombing, Lambok Hermanto (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
In every human society, family bonds are absolutely essential. The most influential and persistent relationships throughout the developmental lifespan are those within families. Moreover, family can serve as a mirror for an individual's identity. Through social status, culture, religion, tribe, and tradition, individuals' identities within their families can be defined. This condition is depicted in the Wei short movie. In this scientific study, the author aims to analyze how the complex meaning of an identity represented in that movie. In order to help the author doing this analysis, Mise En Scene approach from Manon de Reeper and Cultural Identity from Stuart Hall are used for this study. The result of this study indicates that this film represents the complex understanding of Indonesian-Chinese family cultural context.